2014
DOI: 10.1111/1574-6941.12279
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cultivableBacteriafrom the prokaryotic community associated with the carnivorous spongeAsbestopluma hypogea

Abstract: Combining culture-dependent and independent approaches, we investigated for the first time the cultivable fraction of the prokaryotic community associated with the carnivorous sponge Asbestopluma hypogea. The heterotrophic prokaryotes isolated from this tiny sponge were compared between specimens freshly collected from cave and maintained in aquarium. Overall, 67 isolates obtained in pure culture were phylogenetically affiliated to the bacterial phyla Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(81 reference statements)
1
11
0
4
Order By: Relevance
“…Transmission electron microscopy (TEM) images indicate at least three bacterial morphotypes in the species Cladorhiza methanophila Vacelet and Boury-Esnault, 2002 from a mud volcano at the base of the Barbados Accretionary Prism (BAP) (Vacelet et al, 1995; Vacelet and Boury-Esnault, 2002), and reported TEM observations from the Pacific species Lycopodina occidentalis (Lambe, 1893) show that bacteriocytes are abundant in the mesohyl, especially in the filaments, in species without known chemoautotrophic symbionts as well (Riesgo et al, 2007). However, the only known microbiome data currently available for carnivorous sponges is from Dupont et al (2013, 2014), who characterized the microbial community of L. hypogea Vacelet and Boury-Esnault, 1996 from a Mediterranean cave.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images indicate at least three bacterial morphotypes in the species Cladorhiza methanophila Vacelet and Boury-Esnault, 2002 from a mud volcano at the base of the Barbados Accretionary Prism (BAP) (Vacelet et al, 1995; Vacelet and Boury-Esnault, 2002), and reported TEM observations from the Pacific species Lycopodina occidentalis (Lambe, 1893) show that bacteriocytes are abundant in the mesohyl, especially in the filaments, in species without known chemoautotrophic symbionts as well (Riesgo et al, 2007). However, the only known microbiome data currently available for carnivorous sponges is from Dupont et al (2013, 2014), who characterized the microbial community of L. hypogea Vacelet and Boury-Esnault, 1996 from a Mediterranean cave.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, attention was given to Joostella strain A8 because such genus (within the family Flavobacteriaceae, phylum Bacteroidetes) was described only recently and few studies have been addressed to (Quan et al 2008;Kim et al 2011;Hameed et al 2014;Yang et al 2014). Members in the genus have been observed in association with anemones (Du et al 2010), sponges (Jackson et al 2012Dupont et al 2014), fecal pellets (De Troch et al 2010), and sediment (Velmurugan et al 2011). In some cases, antibacterial and algicidal activities by Joostella isolates have been reported (Dupont et al 2014;Yang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Members in the genus have been observed in association with anemones (Du et al 2010), sponges (Jackson et al 2012Dupont et al 2014), fecal pellets (De Troch et al 2010), and sediment (Velmurugan et al 2011). In some cases, antibacterial and algicidal activities by Joostella isolates have been reported (Dupont et al 2014;Yang et al 2014). These reports clearly indicate the wide distribution of members of the genus Joostella in nature and their potential as a source of useful compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunistic bacterium 1A1, isolated from an unhealthy S. domuncula specimen, infected experimentally other healthy sponges. It is phylogenetically related to other marine Pseudoalteromonas species and, especially to one found in a carnivorous sponge [ 51 ]. Besides, considering the pathogenicity of P. agarivorans strain NW4327 toward sponges [ 47 ] and the proliferation of Pseudoalteromonas sp.…”
Section: Discussionmentioning
confidence: 99%